THE LEGITIMACY OF THE EUROPEAN UNION AS A GLOBAL ACTOR ON INTERNATIONAL POLITICAL SCENE UNDERMINED BY THE ENLARGEMENT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The EU enlargement process has stalled over the last decade and there appears to be little prospect of any of the current candidate countries securing accession in the near future. The failed EU enlargement agenda will have significant implications on the confidence of the EU as a global player, and the legitimacy of the EU as a significant political force on the international stage and in relations with third countries is also called into question. The commitment to the enlargement of European Union with North Macedonia and Albania was overshadowed by the demands of Bulgaria set at the level of criteria for North Macedonia for the country’s accession to the EU. On the other hand, accelerated process for enlargement of the European Union with Ukraine, Georgia and Moldova is being advocated. How much such developments affect the legitimacy and credibility of the EU in international relations, but also what is the role of the “soft” power of the Union in the process of enlargement to overcome the national interests of the member states and prevent them from being set up as interests of the Union are questions to which this paper is focused on and provides the answers.